From Individual Responsibility to Regulatory Stewardship: Reconstructing Consumer Protection within Indonesia’s Health Influencer Ecosystem - Denni Boy Saragih; Riswan Marshal; Vivit Puji Puspitasari; Friskha Suhailah Firdaus (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
The proliferation of health influencers on social media has transformed health communication while generating new forms of consumer risk in digital environments. In Indonesia, this phenomenon occurs within a rapidly expanding digital ecosystem, where health information is increasingly mediated by algorithm-driven platforms rather than traditional medical authorities. However, the public authority exercised by health influencers is often not accompanied by professional competence or legal accountability, raising significant concerns for consumer protection. This study examines the legal challenges of consumer protection in digital health content in Indonesia using a normative juridical (doctrinal) approach, combining statutory, conceptual, and comparative analyses. Through legal gap analysis, it finds that existing legal frameworks, particularly the Consumer Protection Law, Health Law, and Electronic Information and Transactions Law, remain inadequate in regulating the legal status, transparency, and accountability of health influencers. The findings show that consumer harm is best understood as distributed harms, systemic and cumulative risks arising from interactions between influencers, platforms, sponsors, and regulatory limitations. In response, this article proposes a regulatory stewardship model that redistributes responsibility across these actors, offering a preventive and ecosystem-based approach to protecting public health in Indonesia’s digital environment.